KAJIAN AKTIVITAS EKONOMI BURUH ANGKUT PEREMPUAN DI PASAR BADUNG - Luh Gede Meydianawathi (PIRAMIDA, 2011)
Balinese women tends to enter the labor market in informal sector. One ofthe unique jobs of Balinese women in the informal sector, is to become laborershaul (carry women) in Badung Market, as the biggest traditional market inDenpasar.This research is using survey and depth interview method. Data collected byobservations and interviews to 30 respondents using questionnaire. The resultsshown that based on the economic activity analysis of respondents, indicated thatthe highest average income of respondents is between Rp 175,000 - Rp 250,000per day, earn by a carry woman that has worked from 5 until over 15 years length.Furthermore, an outpouring of average working hours is above the normalworking hours (> 40 hours per week).The push factors that driving the respondent worked as a carry woman inBadung Market are due to the low level of income, do not have another job, wantto spend leisure time and want to make money themselves. Whereas, the pullfactors are due to follow the call of family or friends, higher labor income, andshort distance to the work place. As a recommendation, it is necessary to form anassociation that protect all the carry women workers at Badung Market, which isalso play a role in organizing, establishing a standard operation procedure, servicefees, which will create an equitable distribution of income among carry women atBadung Market.